Common root causes in recent failures of cranes - Marquez, Anibal Angel (2014)
Catastrophic failure of cranes is a potentially very dangerous event and has often fatal consequences. The failures of two cranes are discussed in this study. Both cranes have different designs, but common root causes have been identified, related to deficiencies in the design and construction of their bases. Striking similarities in failure circumstances are discussed in this study. These include errors in the identification and interpretation of previous symptoms, in the mitigation measures undertaken and in the risks assumed by personnel, due to lack of information and training. The cranes are slender structures subjected to large loads that generate alternate stresses in the bases. The effects and implications of variable loads are often not completely understood or valued by builders and operators, which are used to deal with intrinsically static loads. A normative gap in the identification of responsibilities deriving from the equipment rent or sale contracts has been identified and is discussed. Finally, these failures stress the importance of early indications. Often, what appears to be a minor hitch turns out to be a deadly disaster.